Hidden Resilience in the Life of Adolescents with Involvement in Drug Trafficking - Pessoa, Alex Sandro Gomes (2019)
This paper identifies hidden resilience processes among adolescents and young adults who have hadinvolvement in drug trafficking. The participants were 551 adolescents and young people, aged 12-20 years (M = 16.01;SD = 1.548) from both genders, 55.4% of whom were boys. They were recruited from three social service institutionslocated in the state of São Paulo, which offer services for adolescents with and without a history of involvement in drugtrafficking. To assess rates of resilience, the Child and Youth Resilience Measure was employed. Contrary to expectations,adolescents with greater involvement in drug trafficking had higher rates of resilience. This paper challenges the hegemonicconceptualization of resilience and proposes that more studies of hidden resilience need to be conducted.